A Qualitative Systematic Review of Older Persons’ Perceptions of Health, Ill Health, and Their Community Health Care Needs - Anne Lise Holm; Elisabeth Severinsson (Nursing Research and Practice)
The aim of this qualitative systematic review was to report a synthesis of older persons’ perceptions of health, ill health, and their community health care needs. The review questions were what characterizes older persons’ perceptions of health and ill health? and what are their community health care needs? Ten studies were identified in a systematic search for relevant qualitative papers published between January 2000 and January 2013 in the following electronic databases: PubMed, EBSCOhost/Academic Search Premier, and CINAHL. Publications were evaluated for quality, and a thematic analysis was performed. Two main themes were interpreted on a higher level: reconciliation with how life has become: and desire to regain their identity and sense of self-worth despite disability. Two themes emerged: creating meaning led to the experience of being valued in health care and society and a mental struggle to regain independence with the help of caregivers. Of special interest is the finding of perceptions related to the fear of becoming dependent on caregivers as well as the sorrow and pain caused by encountering caregivers who did not understand their desire to create meaning in their lives or their struggle for autonomy and independency.